PERAN PEMERINTAH SEBAGAI KUNCI UTAMA PENGELOLAAN DANA DESA DI DESA DULUMAI KECAMATAN PAMONA PUSELEMBA KABUPATEN POSO PROPINSI SULAWESI TENGAH - Mantiri, Jeane; Siwi, Cynthia Maria (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2018)
This study aims to analyzed and assess the process of using village funds derived since march 2017, adjusted to priority development program by president Joko Widodo called â€œNAWACITAâ€on the third point of building the outskirtsÂ  of Indonesia from the periphery. The village funds distributed annually are itended to improve the economy of rural communities, and make the village as a productive area, considering Indonesia is an agrarian country consisting of many villages. In accordance with the regional autonomy system adopted by the Indonesian government system, villages have an important role to manage the village funds themselves. The project of this research is the use of village funds in Dulumai Village, Pamona Puselemba sub-district, Poso district, Central Sulawesi Province.Â Keyword:Excellent Product of Rural Area, Management of Village Fund.